Perencanaan Pembelajaran Berbasis Wahdatul Ulum (Studi Pada Prodi PAI UIN Sumatera Utara Medan) - Rahmat Rifai Lubis; Sania Aqhila; Ahda Manurung; Devi Yani Pasaribu; Muhammad Suheri; Asti Indah Lestari Nasution (Edusifa: Jurnal Pendidikan Islam, 2024)
ABSTRACT This study aims to analyze the implementation of learning design (RPS) by lecturers at UIN North Sumatra, especially for lecturers at PAI study program, which in its implementation has the Wahdatul Ulum concept. The focus of the study is on two things, namely the characteristics of wahdatul ulum-based learning and the wahdatul ulum-based Semester Learning Plan Model (RPS). The research method used is qualitative based on descriptive studies. Data collection techniques used are observation, interviews, and documentsation studies. The data obtained were then analyzed using the Miles and Huberman technique, namely data reduction, data display, and drawing conclusions. The results of the study explain that the implementation of learning planning based on Wahdatul Ulum is something that must be applied among UIN North Sumatra lecturers. The existence of its own characteristics or characteristics owned by UIN North Sumatra, namely Wahdatul Ulum, will certainly change all existing concepts, both in the form of lecturer lesson plans, learning strategies, learning evaluations and even learning materials or courses given. In this way, it cannot be denied that lecturers are required to make and understand the concept of Wahdatul Ulum in making lesson plans. Keyword: Learning Planning, Wahdatul Ulum, Islamic Religious Education